2013
DOI: 10.1176/appi.ajp.2013.12091163
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Genotype Combinations That Can Predict the Outcome of the Treatment of Alcohol Dependence Using the 5-HT3 Antagonist Ondansetron

Abstract: Objective Previously, we reported that the 5′-HTTLPR-LL and rs1042173-TT (SLC6A4-LL/TT) genotypes in the serotonin transporter gene predicted a significant reduction in the severity of alcohol consumption among alcoholics receiving the 5-HT3 antagonist ondansetron. In this study, we explored additional markers of ondansetron treatment response in alcoholics by examining polymorphisms in the HTR3A and HTR3B genes, which regulate directly the function and binding of 5-HT3 receptors to ondansetron. Method We ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 46 publications
(50 reference statements)
2
85
1
Order By: Relevance
“…Also, further exploration of genetic underpinnings of both disorders is important to individualize and optimize future psychosocial and pharmacological treatment. Theoretically, individuals with a genetic susceptibility for ADHD and SUD might benefit from different treatment options than individuals without such hereditary risk factors (34).…”
Section: Discussionmentioning
confidence: 99%
“…Also, further exploration of genetic underpinnings of both disorders is important to individualize and optimize future psychosocial and pharmacological treatment. Theoretically, individuals with a genetic susceptibility for ADHD and SUD might benefit from different treatment options than individuals without such hereditary risk factors (34).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with ondansetron have shown a reduction in the amount of alcohol used and a longer remission in persons with early-onset AUD (108). In addition, a polymorphism in the starting region of the serotonin carrier gene has been shown to affect the response to ondansetron, and in carriers of the long LL allele, ondansetron reduced the amount of alcohol used (109). Another experimental study reported that ondansetron might reduce alcohol consumption in women with the LL 5-HTTLPR genotype, while it was not effective in women with the SS/SL 5-HTTLPR genotype (110).…”
Section: Ondansetronmentioning
confidence: 99%
“…A more recent study demonstrated ondansetron's efficacy in patients with variants in genes encoding the serotonin transporter or serotonin-3 receptors [66].…”
Section: Serotonergic and Dopaminergic Medicationsmentioning
confidence: 99%